Helical preorganization of molecules drives solid-state intermolecular acyl-transfer reactivity in crystals: structures and reactivity studies of solvates of racemic 2,6-Di-O-(4-fluorobenzoyl)-myo-inositol 1,3,5-orthoformate - Krishnaswamy, Shobhana; Shashidhar, Mysore S.; Bhadbhade, Mohan M. (Crystal Growth & Design, 2017)
Racemic 2,6-di-O-(4-fluorobenzoyl)-myo-inositol 1,3,5-orthoformate yielded structurally dissimilar solvent-free and solvated crystals depending upon the solvent of crystallization. The solvated crystals exhibited helical assembly of host molecules, due to the interaction of the guest molecules with the orthoformate moiety of the host. Some of the solvates showed specific but incomplete benzoyl group transfer reactivity below the phase transition temperature, whereas the reaction in solvent-free crystals led to a mixture of several products. These results reveal the necessity of helical molecular packing of the reacting molecules in their crystals to facilitate specific intermolecular acyl transfer reactivity. The crystal, structures of the fluorobenzoate solvates were similar to those of the solvates of the analogous chloro and bromobenzoates. The latter could be thermally :transformed into their solvent-free form via melt crystallization, resulting in the conversion of a helical molecular packing into a nonhelical molecular packing.